A custom software solution for forensic mtDNA analysis of MiSeq data. (December 2015) - Holland, Mitchell; McElhoe, Jennifer
Abstract: The use of a next generation sequencing (NGS) approach for mitochondrial (mt) DNA analysis in forensic casework is imminent. A feature of the NGS approach is the ability to detect and report mtDNA heteroplasmy, which will significantly enhance the discrimination potential of the testing method. A single software solution that allows for robust and user-friendly analysis of NGS-derived mtDNA sequence is not readily available, especially when considering heteroplasmy. This communication outlines the desired features of a software package for forensic applications, and the progress made towards those aims with the development of a custom version of NextGENe ® .